2017
DOI: 10.1038/s41598-017-07755-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of human Vaccinia-Related Kinases (VRK) bound to small-molecule inhibitors identifies different P-loop conformations

Abstract: The human genome encodes two active Vaccinia-related protein kinases (VRK), VRK1 and VRK2. These proteins have been implicated in a number of cellular processes and linked to a variety of tumors. However, understanding the cellular role of VRKs and establishing their potential use as targets for therapeutic intervention has been limited by the lack of tool compounds that can specifically modulate the activity of these kinases in cells. Here we identified BI-D1870, a dihydropteridine inhibitor of RSK kinases, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 56 publications
0
45
0
2
Order By: Relevance
“…(B)], though this needs further investigation. It was concluded that the P‐loop is a highly flexible region in all VRK1 crystal structures and could be traced in only one of chains in the inhibitor complex (Chain A of PDB ID 5UKF) . Nonetheless, our NMR titration shows that the residues in the P‐loop (Gln45, Gly45, Gly46, and Gly49) are affected upon AMP‐PNP binding, validating their interaction.…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…(B)], though this needs further investigation. It was concluded that the P‐loop is a highly flexible region in all VRK1 crystal structures and could be traced in only one of chains in the inhibitor complex (Chain A of PDB ID 5UKF) . Nonetheless, our NMR titration shows that the residues in the P‐loop (Gln45, Gly45, Gly46, and Gly49) are affected upon AMP‐PNP binding, validating their interaction.…”
Section: Resultsmentioning
confidence: 56%
“…Although the comparison provides a structural perspective, in future, it would be necessary to study the enzyme kinetics of these inhibitors and AMP‐PNP, lacking till‐date, to further enhance our understanding into VRK1 activity and specificity. In conclusion, as VRK1 is regarded as an important cancer drug target due to its enhanced expression levels in many cancer tissues, the molecular insights on the VRK1 interaction with AMP‐PNP presented here, along with the earlier inhibitor complexes, could be used to develop a pharmacophore model followed by fragment screening, toward identifying effective VRK1‐specific inhibitors.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations